(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The authors present their II contribution within the research field on citrus mites in Italy, referring it to the suborder Gamasida with the families Phytoseiidae Berlese and Ascidae Voigts & Oudemans: The key intended for the identification of genera and species found by them and the relative biology notes are here reported.